Use of machine learning and weather predictions to bridge the gap between consumer demands and the market requirements of food crops - Hasan, Raad; Hossain, Romaiya; Ahmed, Farah; Md. Iftekhar Islam, Md. Iftekhar (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.